Caça e segurança alimentar em comunidades ribeirinhas do médio Xingu - SOUSA, Girlian Silva de (Universidade Federal do Pará, 2017)
Hunting is an extremely complex issue, due to the serious impact on the environment, but also because game meat is one of the main sources of animal protein for the traditional Amazonian people. This essay discusses subsistence hunting and the lack of access regarding river communities from the Reserva Extrativista do Rio Iriri to food security policies. It aims to discuss the socioeconomic contribution of subsistence hunting, and to bring evidences of the difficult situation in which these families live while trying to gain access to food products and public services in general. To achieve these goals, this paper embraces the theme from an economic and anthropological perspective, by using ethnographic resources to show evidences of the relations between man and environment, as well as the interaction between the economic sector and the other sectors in social life. For this discussion, the theoretical and methodological support from Maurice Godelier, Karl Polanyi, Pierre Bourdieu, Jorge Gasché Suess and Napoleón Vela Mendoza was used, as well as concepts of microeconomics.